Investigating the application of FDM 3D printing pattern in preparation of patient-tailored dosage forms. Issue 1 (1st February 2019) - Nukala, Pavan Kumar; Palekar, Siddhant; Solanki, Nayan; Fu, Yige; Patki, Manali; Sohatee, Ali A; Trombetta, Louis; Patel, Ketan
Aim: The aim of this work was to investigate the effect of printing pattern on physical attributes and dissolution of fused deposition modeling 3D printed caplets.Methods: Hydrochlorothiazide-loaded polyvinyl alcohol filaments were prepared by hot melt extrusion. Caplets printed in hexagonal (HexCap), diamond infill (DiaCap) in three different sizes using fused deposition modeling 3D printer and evaluated for hardness, disintegration and dissolution.Results: DiaCaps exhibited higher hardness than HexCaps. Disintegration time for HexCaps was <20 mins. while DiaCaps took 25–40 mins. DiaCaps showed 20–30% lower release at all time points compared with HexCaps.Conclusion: Although composition, processing parameters were same, mere change in printing pattern alters disintegration and dissolution. Findings of this study can be invaluable in developing patient-tailored medicines.